Kepemimpinan Kepala Sekolah dalam Membangun Budaya Organisasi Perspektif Islam - Robbani, Afifuddin Ahmad (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2025)
The importance of building an organizational culture in schools, especially with regard to efforts to achieve school education goals and improving school quality, is a reason why leadership needs to have several sustainable principles. Organizational culture can be said to be good if it is able to mobilize all personnel consciously and is able to contribute to optimal work effectiveness and productivity. In relation to schools as an organization, it is of course very necessary to understand how to identify ineffectiveness within the organization so that it can improve the quality of the school. Leadership from an Islamic religious perspective is certainly a reference for organizational cultural patterns based on verses from the Koran and hadith along with their explanatory interpretations. The research method used in this research is library research or literature study based on several references in the form of journal articles, books and verses from the Koran along with their interpretations contained in Arabic books which discuss leadership in building an organizational culture from an Islamic religious perspective.The conclusion of this literature review can be understood that the principal's leadership in building an organizational culture from an Islamic religious perspective is based on several principles, including; Being an example/example as stated in Q.S Al-Ahzab verse 21, creating a conducive environment as stated in al-Baqarah verse 205, understanding the duties and functions as stated in surah Shad verse 26, showing trust as stated in al-Imran verse 159, and having exemplary qualities as stated in surah yusuf verse 54. Some of these things of course refer to the principles of leadership or organizations that existed during the time of the prophet Muhammad and previous prophets. Leadership within the school certainly creates a school organizational culture that is harmonious and related to each other in terms of policy.